1997
DOI: 10.1002/ijch.199700022
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Overpotential Dependence of Long‐Range Electron Transfer across a Self‐Assembled Monolayer with Pendant Ruthenium Redox Centers

Abstract: Mixed monolayers containing an electro active thiol, HS(CHJ1sCONHCHJ>yRu(NH3)sz+13+, and a diluent thiol, HS(CHz)ISCOOH,on gold electrodes are examined in acetonitrile electrolyte (0.1 M LiCIOJ as a function of overpotential and temperature. Kinetic and thermodynamic parameters from ca. -45 to +20°C are obtained by cyclic voltammetry and chronoamperometry. Reorganization energies obtained from Tafel plots and Arrhenius plots both yield a reorganization energy of 0.8 eV for the redox centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Reorganization energies of both the oxidized and reduced forms can be obtained from Tafel plots of redox couples attached to self-assembled monolayers (SAMs) on electrodes [24][25][26][27][28][29][30][31][32][33][34][35][36]. In this work, we describe the electron tranfer kinetics of 4-amino-TEMPO Å coupled to a SAM with pendant carboxylic acid moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Reorganization energies of both the oxidized and reduced forms can be obtained from Tafel plots of redox couples attached to self-assembled monolayers (SAMs) on electrodes [24][25][26][27][28][29][30][31][32][33][34][35][36]. In this work, we describe the electron tranfer kinetics of 4-amino-TEMPO Å coupled to a SAM with pendant carboxylic acid moieties.…”
Section: Introductionmentioning
confidence: 99%
“…The aligned orientation of alkanethiol molecules is one of the most attractive features of the self-assembled monolayers (SAMs) of such molecules. The monolayers of various types of alkanethiol derivatives with covalently tethered electroactive groups have been investigated in detail. In such SAMs, it is expected that the orientation of the electroactive moiety, lateral interaction among the active centers, and microenvironment for them are highly regulated. The structure of the SAM may be governed by a number of factors including alkyl chain length, counterion involved in the redox reaction, and surface density of the thiol.…”
Section: Introductionmentioning
confidence: 99%
“…Chidsey and co-workers reported on this class of eSAM in 1990, , and they showed that it is possible to correlate the shift in the redox potential of the ferrocene moiety to the length of the alkyl chain. Subsequently, eSAMs have been extensively studied to better understand SAM structure and functionality, electrochemical desorption of alkylthiols, the formation and exchange of alkylthiol SAMs, ,, and fundamental aspects of electron transfer. , One conclusion that has emerged from these types of studies is that eSAMs containing exclusively ferrocene-terminated alkylthiols are disordered. , Consequently, mixed monolayers, composed of ferrocene-terminated alkylthiols and non-electroactive, shorter chain alkylthiols, are typically employed to improve ordering within the monolayer. , Additionally, the Schmittel and Plaxco groups have recently demonstrated that ferrocene-terminated eSAMs can decompose over the span of just minutes due to the instability of the ferrocenium redox state. Despite this instability, eSAMs consisting of ferrocene-terminated alkylthiols are considered to be well-defined model systems.…”
Section: Introductionmentioning
confidence: 99%